Immunohistochemical assessment and clinical, histopathologic, and molecular correlates of membranous somatostatin type-2A receptor expression in high-risk pediatric central nervous system tumors - Lazow, Margot A.; Fuller, Christine; Trout, Andrew T.; Stanek, Joseph R.; Reuss, Jaime; Turpin, Brian K.; Szabo, Sara; Salloum, Ralph (Frontiers in Oncology, 2022)
177Lu-DOTATATE, a radionuclide therapy that binds somatostatin type-2A receptors (SST2A), has demonstrated efficacy in neuroendocrine tumors and evidence of central nervous system (CNS) penetration, supporting potential expansion within pediatric neuro-oncology. Understanding the prevalence of SST2A expression across pediatric CNS tumors is essential to identify patients who may benefit from somatostatin receptor-targeted therapy and to further elucidate the oncogenic role of SST2A. SST2A immunohistochemistry (IHC) was performed on tumor specimens and interpreted by an experienced pathologist (blinded), utilizing semi-quantitative scoring of membranous expression within viable tumor. Immunoreactive cell percentage was visually scored as 0 (none), 1 (<10%), 2 (10-50%), 3 (51-80%), or 4 (>80%). Staining intensity was scored as 0 (none), 1 (weak), 2 (moderate), or 3 (strong). Combined scores for each specimen were calculated by multiplying percent immunoreactivity and staining intensity values (Range: 0-12). A total of 120 tumor samples from 114 patients were analyzed. Significant differences in SST2A IHC scores were observed across histopathologic diagnoses, with consistently high scores in medulloblastoma (mean±SD: 7.5±3.6 [n=38]) and meningioma (5.7±3.4 [n=15]), compared to minimal or absent expression in ATRT (0.3±0.6 [n=3]), ETMR (1.0±0 [n=3]), ependymoma (grades I-III; 0.2±0.7 [n=27]), and high-grade glioma (grades III-IV; 0.4±0.7 [n=23]). Pineoblastoma (3.8±1.5 [n=4]) and other embryonal tumors (2.0±4.0 [n=7]) exhibited intermediate, variable expression. Among medulloblastomas, SST2A IHC scores were higher in non-SHH (8.5±3.1) than SHH (5.0±3.3) molecular subgroups (p=0.033). In a subset of paired primary and recurrent specimens from four patients, SST2A IHC scores remained largely unchanged. High membranous SST2A expression was demonstrated in medulloblastoma, meningioma, and some rarer embryonal tumors with potential diagnostic, biologic, and therapeutic implications. Somatostatin receptor-targeted therapy such as 177Lu-DOTATATE deserves further investigation in these highly SST2A-expressing pediatric CNS tumors.